(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2025)
The intellectual and philosophical arena has witnessed radical changes under the shadow of postmodern thought. Philosophers and critics have begun to question many of the concepts prevalent under the thought of the modern era, which concern the concepts of absolute truth, objectivity, and even language. Literature in general had a large share of this transformation, as the postmodern era witnessed a remarkable development in literary styles. Literature at this stage became more diverse and free in expression, as literary genres overlapped and styles blended, allowing for the emergence of new styles that challenge traditional rules that might lead to monotony. The novel is one of the literary arts that was greatly influenced by postmodernist thought, as it witnessed a major transformation in its structure and styles, becoming more diverse in its treatment of topics. Literary forms have become fragmented and pluralistic, containing more than one narrative level while presenting different and conflicting visions within the same text. They have also witnessed the emergence of new techniques: deconstruction, temporal manipulation, and intertextuality, where writers resort to breaking the chronological sequence of events and drawing on numerous cultural and intellectual texts to enrich the narrative text. This study seeks to uncover the manifestations of postmodernist thought in the novel "Ya Banat Iskandaria" (O Girls of Alexandria) by Edwar El-Kharrat. The autobiographical novel focuses on aspects of his life during his youth during the 1940s and 1950s. The study reveals how El-Kharrat employs narrative elements to reflect the influence of postmodernist thought on the author’s writing. Which appears clearly in the novel, with an analysis of the elements of narrative in the novel that is the subject of the research.